A new class of flavonol-based anti-prostate cancer agents: Design, synthesis, and evaluation in cell models. Issue 17 (1st September 2016) - Li, Xiang; Chen, Guanglin; Zhang, Xiaojie; Zhang, Qiang; Zheng, Shilong; Wang, Guangdi; Chen, Qiao-Hong
Graphical abstract: Abstract: Flavonoids are a large class of polyphenolic compounds ubiquitously distributed in dietary plants with an array of biological activities. Flavonols are a major sub-class of flavonoids featuring a hydroxyl group at C-3. Certain natural flavonols, such as quercetin and fisetin, have been shown by in vitro cell-based and in vivo animal experiments to be potential anti-prostate cancer agents. However, the Achilles' heel of flavonols as drug candidates is their moderate potency and poor pharmacokinetic profiles. This study aims to explore the substitution effect of 3-OH in flavonols on the in vitro anti-proliferative potency against both androgen-sensitive and androgen-insensitive human prostate cancer cell lines. Our first lead flavonol (3′, 4′-dimethoxyflavonol), eight 3- O -alkyl-3′, 4′-dimethoxyflavonols, and six 3- O -aminoalkyl-3′, 4′-dimethoxyflavonols have been synthesized through aldol condensation and the Algar–Flynn–Oyamada (AFO) reaction. The WST-1 cell proliferation assay indicates (i) that all synthesized 3- O -alkyl-3′, 4′-dimethoxyflavonols and 3- O -aminoalkyl-3′, 4′-dimethoxyflavonols are more potent than the parent 3′, 4′-dimethoxyflavonol and the natural flavonol quercetin in suppressing prostate cancer cell proliferation; and (ii) that incorporation of a dibutylamino group to the 3-OH group through a three- to five-carbon linker leads to the optimal derivatives with up to 292-fold enhanced potency as compared with the parent flavonol. Flow cytometry analysis showed that the most potent derivative22 can activate PC-3 cell cycle arrest at the G2 /M phase and induce PC-3 cell apoptosis. No inhibitory ability of22 up to 50 μM concentration was observed against PWR-1E normal human epithelial prostate cells, suggesting its in vitro safety profile. The results indicate that chemical modulation at 3-OH is a vital strategy to optimize flavonols as anti-prostate cancer agents.